EVALUASI EFEKTIFITAS PENGEMBANGAN INFRASTRUKTUR JARINGAN LAN DAN INTERNET TERHADAP PROGRAM SEKOLAH PENGERAK DI SMAN 13 PADANG - Syaflan Sandi Harta Putra; Ambiyar Ambiyar; Wakhinuddin Wakhinuddin; Nizwardi Jalius; Bulkia Rahim (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2022)
The Motivating School Program is an effort to realize the vision and mission of Indonesian Education in realizing an advanced Indonesia that is sovereign, independent, and has personality through the creation of Pancasila Lessons. The Motivating School Program focuses on developing holistic student learning outcomes that include competencies (literacy and numeracy) and character, starting with superior human resources (principals and teachers). To realize the Driving School Program, there are five driving school program interventions that must be carried out, 1) Consultative and asymmetric assistance, 2) Strengthening human resources in schools, 3) learning with a new paradigm, 4) Database planning, 5) Digitizing schools. School digitization is a priority aspect of the driving school program at SMAN 13 Padang. Needs analysis was carried out using field observations and interviews with the Principal and IT Admin. Observations and interviews are useful to get real problems in the field directly and accurately. The results of the analysis and evaluation of the development of LAN and Internet network infrastructure at SMAN 13 Padang provide an apology and a very positive impact in supporting the learning and teaching process with 93% traffic usage of internet facilities and 400 Mbps internet capacity usage in the school academic environment. This driving school program is very helpful in realizing the vision and mission of Indonesian Education. Keywords: Motivating School, Digital, Infrastrukture, Network, Internet